2000
DOI: 10.1002/(sici)1097-0096(200003/04)28:3<115::aid-jcu2>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reserve capacity in patients with hyperlipidemia

Abstract: Purpose. Because recent data are conflicting, it is not certain whether hyperlipidemia is an independent risk factor for cerebrovascular diseases. Decreased cerebrovascular reserve capacity refers to the decreased ability of the cerebral arterioles to adapt in critical conditions and probably predicts a higher risk of stroke. The aim of this study was to compare cerebrovascular reserve capacity in hyperlipidemic patients and healthy controls using transcranial Doppler sonography.Methods. Thirty-four hyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…CRC was normal in this patient group. Others, using transcranial Doppler, could not detect any differences between the CVR capacity of hypercholesterolemic patients and that of the normal subjects (Kerenyi et al, 2000).…”
Section: Familiar Hypercholesterinemiamentioning
confidence: 91%
“…CRC was normal in this patient group. Others, using transcranial Doppler, could not detect any differences between the CVR capacity of hypercholesterolemic patients and that of the normal subjects (Kerenyi et al, 2000).…”
Section: Familiar Hypercholesterinemiamentioning
confidence: 91%
“…Areas with low CVR might be vulnerable during marked blood pressure changes and this insufficient compensatory mechanism may not be able to prevent sudden CBF alterations. Experimental studies have shown that the CVR may also depend on the underlying diagnosis related to the intracranial pathology (Brauer et al 1998, Kerenyi et al 2000, Piechnik et al 2001. Current knowledge is still fragmentary as regards the utility of these vasodilatory tests in establishing the appropriate management via determination of the CVR in different brain regions in the event of an intact circulation (Sato et al 1984), although this could be of clinical interest.…”
mentioning
confidence: 99%
“…Experimental studies have shown that the CVR may also depend on the underlying diagnosis related to the intracranial pathology (Brauer et al. 1998, Kerenyi et al. 2000, Piechnik et al.…”
mentioning
confidence: 99%
“…In our study, we found a positive association between basal circulation and HDL cholesterol, whereas acetazolamidestimulated blood flow had a significant positive association with HDL cholesterol and it correlated negatively with triglyceride. These data agree with the atherogenic dyslipidemia found previously in diabetic patients but conflict with the results of Kerényi et al, who could not detect any difference in the reserve capacity between hyperlipidemic patients and healthy subjects using transcranial Doppler ultrasound (20). It is a possible explanation that the patients participating in the latter study had isolated hypercholesterolemia and no diabetes, an only slightly elevated triglyceride level, and a normal HDL level.…”
Section: Discussionmentioning
confidence: 99%